Prevalence and predictors of pap smear practice among staff of a Public University in Nilai, Negeri Sembilan - Mohd Razi N.A.; Manaf R.A.; Ismail S. (Faculty of Medicine and Health Sciences, 2024)
Indexed by SCOPUS